Clinical PET and PET/CT - Jadvar, H.; Parker, J.A (Springer London : Imprint: Springer, 2005)
A practical manual covering the full spectrum of PET and PET/CT imaging, now in common clinical practice, this book includes images of normal variants, artifacts, and pathologic conditions. Indications for and the relative clinical value of PET in the armamentarium of diagnostic medical imaging are reviewed. The information in the book is organized to be brief, concise, easy-to-understand and readily accessed. This book is intended for all health practitioners who need a concise reference and review of PET imaging indications, protocols and clinical applications. It will be useful to radiologists, nuclear medicine physicians, and clinicians who refer their patients to PET Centers for diagnostic imaging, including neurologists, neurosurgeons, psychiatrists, cardiologists, internists, and oncologists. Radiologic and nuclear medicine technologists, and physicians in training will also benefit from this work.